Evaluation of a double-shell integrated scanning lens antenna - Costa, Jorge R. (2014)
This letter presents the design and evaluation of a high dielectric constant double-material integrated lens antenna for multibeam or scanning applications. The lens is formed by two shaped embedded shells of different material permittivity to enhance both power transmission across the lens interfaces and the lens scanning characteristics over a broad frequency range, when the feeds are integrated at the lens base. Design is based on geometrical optics formulation and the lens performance is evaluated using the classic hybrid geometrical optics/physical optics approach (GO/PO). The proposed lens concept is experimentally validated with a fabricated MACORtrade/acrylic prototype, showing less than 1-dB scan loss up to plusmn20deg with Gaussicity better than 95% over 40% frequency band at millimeter waves.